CORRUPTION AND EDUCATION: IMPACT ON CHILDREN AND SOCIETY - Austin Mardon; Khushi Shah (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2024)
The Oxford English Dictionary defines corruption as dishonest or illegal behaviour, especially of people in authority. Education is arguably one of the most important aspects of life as with such a lot of doors are opened for individuals, which are not offered to those without. Generation after generation the power and importance of education is only further highlighted, thus more and more children are pursuing higher education. As such, the number of students enrolled in schooling worldwide has been on an upwards trajectory, with an increase of over 150 million students since 2000 for secondary school and around 82 million since 2000 for primary school (Statista, 2022). Furthermore, the completion rate of primary school was close to 90% in 2019 and 76% for secondary school (Statista, 2022). Education can provide individuals with so many options and aid in their life path by increasing the aspects of stability in life, financial stability, equality between individuals worldwide, self-dependence, confidence, provides safety, and helps one reach their goals (Nair, 2022). In Canada itself, more than 1.4 million students are enrolled in a Canadian University, and 2.2 million students are enrolled in some form of postsecondary education (Universities Canada, 2018).